2022
DOI: 10.2478/fv-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Antibiotic Resistance Profiles of Methicillin-Resistant Staphylococcus Aureus (Mrsa) in Layer Chickens in Kebbi, Nigeria

Abstract: Antimicrobial resistance (AMR) is a global health threat, and antimicrobial use in animal production for growth enhancement or prophylaxis contributes to the development of AMR. A cross-sectional study was conducted to investigate the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) in poultry and farm attendants in Kebbi, North-Western Nigeria. A total of 207 cloacal and nasal swabs were randomly collected from four farms comprising 50 samples from each poultry farm and only 7 samples from far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…All the phenotypically positive MRSA isolates used in this study harbored the mecA gene. This finding agrees with Gaddafi et al (2021) and Gaddafi et al (2022), who reported that all the phenotypic MRSA isolates from livestock and poultry harbored the mecA gene. Furthermore, Umaru et al (2014), Rodrigues et al (2017), andAliyu et al (2020) reported the presence of mecA in phenotypically positive MRSA isolates.…”
Section: Discussionsupporting
confidence: 93%
“…All the phenotypically positive MRSA isolates used in this study harbored the mecA gene. This finding agrees with Gaddafi et al (2021) and Gaddafi et al (2022), who reported that all the phenotypic MRSA isolates from livestock and poultry harbored the mecA gene. Furthermore, Umaru et al (2014), Rodrigues et al (2017), andAliyu et al (2020) reported the presence of mecA in phenotypically positive MRSA isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Animal feces are recognized as the primary source of pathogenic E. coli. The close proximity between livestock and their environment facilitates the transmission of pathogenic bacteria among animals and between animals and the environment (Gaddafi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli is the predominant bacterium associated with bacterial infections in livestock, causing significant health problems, increased mortality, reduced production, and higher costs for disease prevention and treatment. A wide range of antimicrobials is commonly used in livestock production, primarily administered orally, to prevent and treat diseases and enhance growth and productivity (Gaddafi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%